supprimer les parentheses dans les expressions suivantes puis reduire . C = -6t - ( 9t + 11 ) - 5 D = 3 + ( 15y² - 5y + 3 ) - ( - 13y + 9 + 3y² ) E = -3p + ( - 7p + 3p² - 6 ) +2p - ( - 12p² - 6p + 9 ) F = 5n² - ( 2n² - 6n + 9 ) + ( -6n + 12 - 4n² )

2

Réponses

Meilleure réponse !
  • carys
  • Modératrice confirmée
2013-03-11T21:10:19+01:00

C = -6t - ( 9t + 11 ) - 5      

C = -6t - 9t - 11 - 5

C = -15t - 16

 

D = 3 + ( 15y² - 5y + 3 ) - ( - 13y + 9 + 3y² )      

D = 3 + 15y² - 5y + 3 + 13y - 9 - 9y²

D = 6y² + 8y - 3

 

E = -3p + ( - 7p + 3p² - 6 ) +2p - ( - 12p² - 6p + 9 )    

E = -3p - 7p + 3p² - 6 + 2p + 12p² + 6p - 9

E = 15p² - 2p - 15

 

F = 5n² - ( 2n² - 6n + 9 ) + ( -6n + 12 - 4n² ) 

F = 5n² - 2n² + 6n - 9 - 6n + 12 - 4n² F = -n² + 3   voilà :)   
2013-03-11T21:15:17+01:00

C = -6t-9t-11-5 = -15t -16

D = 3+15y²-5y+3 +13y-9-3y² = 12y² +8y -3

E = -3p-7p+3p²-6+2p+12p²-6p-9 = 15p² -14p -15

F = 5n²-2n²+6n-9-6n+12-4n² = -n² +3